Arbitration and Public Policy: 2016 Goff Lecture. Issue 1 (30th June 2016) - French, Robert
ABSTRACT: Commercial arbitration being contractually based is a matter of private law. Its effectiveness depends upon legislative support defined by external public policy considerations. Those considerations invite scrutiny of the costs and benefits of commercial arbitration including its effect on the development of commercial law and an appropriate balance between arbitral mechanisms and commercial courts. The growth of commercial arbitration and its application in sensitive areas such as consumer contracts of adhesion may enliven public policy responses. Internal constraints in relation to arbitrability and public policy limits on enforcement play a part in enabling arbitration to function in a way that is sensitive to the larger social and political environment in which it is conducted.